THE RULES OF FI'IL AND THE WISDOM OF LIFE IN ISLAMIC EDUCATION - Dika Sabila (Jurnal Eduslamic, 2025)
This study aims to analyze the relationship between fi'il rules in Arabic and the teaching of values and life lessons. Fi'il rules, which cover aspects of time (madhi, mudhari', and amr), form of action, and actor, not only function as grammatical elements in Arabic grammar, but also have deep philosophical and ethical dimensions. Using a qualitative approach with a literature review method, this study examines key texts such as grammar books, the Quran, and classical and contemporary Islamic educational works. The results of the study indicate that understanding the structure and meaning of fi’il can be a strategic tool in instilling life values such as responsibility, discipline, diligence in doing good deeds, and spiritual awareness. Fi’il amr, for example, is frequently found in the verses of the Qur’an as a command to perform good deeds, avoid prohibitions, and build noble character. Thus, the study of fi’il rules can be used as an important tool in character education and noble ethics, especially in the context of integrative and value-based Arabic language learning.